Covid – 19 Pandemic and Its Influence on The Level of Preparedness of Graduating Students for The Upcoming Licensure Examination - Emmanuel Onsay; Patric Carl Pardiñas; Kayla Mae Tañegra (MASI Mandiri Edukasi, 2023)
Preparedness plays an essential role in taking the licensure examination, but due to the implications of the Covid -19 pandemic on the general population, many are concerned about its influence on the student's level of preparedness for their upcoming licensure examination. This study investigated whether the Covid -19 pandemic and the students' demographic profile influence their financial, mental, academic, and learning environment preparedness. An online survey questionnaire was distributed to the graduating students enrolled in Partido State University board courses during 2022-2023. The collected data was analyzed using ordinal logistic regression. The responses showed that financial, learning environment, mental, and academic preparedness received weighted means of 2.67, 3.46, 2.99, and 2.42, respectively. Meanwhile, the Covid -19 influence received an overall weighted mean of 5.01. These findings indicate that most students believe their financial, mental, and academic preparedness levels are low, while they perceive their environmental preparedness level as high. Despite this, most believe that the Covid - 19 pandemic was somewhat influential and beneficial to their preparedness. Lastly, the ordinal regression model revealed that only the age of the students is statistically significant at 10%. In contrast, the rest of the variables regarding the socio-demographic profile of the students and the perceived Covid -19 influence are not significant at all levels.